Legal Analysis of The Cancellation of The Recording of Transfer of Ownership Rights to Land Based on The Deed of Grant in Central Java - Santi, Santi (TABELLIUS: Journal of Law, 2024)
This study analyzes the cancellation of the recording of the transfer of land ownership rights based on the deed of gift with a focus on the Decree of the Head of the Regional Office of the National Land Agency of Central Java Province Number 02/Pbt/BPN-33/I/2024. The legal procedures followed and their legal impact on the related parties, both from a civil and agrarian law perspective, are the main focus. This study uses a normative legal approach with a case study method. The results of the study indicate that although the procedures are in accordance with applicable regulations, there are obstacles in their implementation, mainly due to the lack of public understanding of proper legal procedures and conflicts of interest between the parties involved. This study makes an important contribution to the development of agrarian law in Indonesia. The results of the study indicate that the procedures followed in the cancellation of the transfer of rights have been in accordance with applicable provisions, but there are several obstacles in its implementation. These obstacles include the lack of public understanding of the correct legal procedures and the existence of conflicts of interest between the parties involved.